Research on data product and their circulation regulatory framework - XIONG Yun; ZHU Yangyong (大数据)
The orderly advancement of data circulation and the effective regulation of the data market through coordinated deployment are the important issue. Addressing challenges such as the low identifiability of data circulation targets and the difficulties in managing the negative externalities of data, this paper defined the forms of data circulation targets from the perspectives of measurement, transmission, and security, proposing identifiable boxed data products as circulation targets. Furthermore, based on these boxed data products, the contents involved in the regulatory system for data product circulation were clarified and a practical regulatory framework for data products was introduced. This framework integrates regulatory indicators at each stage of design, production, and circulation, enabling rapid and effective identification and management of circulation risks.